2021
DOI: 10.3390/v13020304
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Viral Load and the Clinical Course of COVID-19

Abstract: To predict the clinical outcome of coronavirus disease-2019 (COVID-19), we examined relationships among epidemiological data, viral load, and disease severity. We examined viral loads of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) in fatal (15 cases), symptomatic/survived (133 cases), and asymptomatic cases (138 cases) using reverse transcription quantitative real-time PCR (RT-qPCR). We examined 5,768 nasopharyngeal swabs (NPS) and attempted to detect the SARS-CoV-2 genome using RT-qPCR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 25 publications
(25 reference statements)
2
43
0
Order By: Relevance
“…Nonetheless, the impact of viral load on adults may differ from its effect on children. It is widely reported that viral load is higher in symptomatic than asymptomatic COVID-19 adults ( 30 ). The data available in the pediatric population are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the impact of viral load on adults may differ from its effect on children. It is widely reported that viral load is higher in symptomatic than asymptomatic COVID-19 adults ( 30 ). The data available in the pediatric population are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of these data is whether there are differences between age groups, especially the often-quoted assumption that children and adolescents are more likely to be asymptomatic following infection. Early data suggested that asymptomatic disease was indeed inversely correlated with age 17 . However, the Real-time Assessment of Community Transmission 2 (REACT-2) UK national study considered asymptomatic disease in a large cohort of 106,000 adults sampled by specific antibody tests during the first wave of the pandemic in the UK (March to June 2020); 5,544 tested positive, of whom one-third had reported no symptoms, although this rose to more than half of those older than 65 years 6 .…”
Section: How Common Is Asymptomatic Infection?mentioning
confidence: 99%
“…Specific molecular signatures of immune profiling have indicated that delayed adaptive immune responses are correlated with poorer outcomes from SARS-CoV-2 infection [ 48 , 95 , 96 ]. In addition, high viral titres at a range of sampling sites (mostly naso/oropharyngeal, but also saliva, sputum, blood, plasma, urine and stool) have been associated with disease severity [ 97 , 98 ], although further work is required to better understand the relationship between viral titres, severity, and impaired adaptive immunity. A putative explanation for the pathophysiology of severe COVID-19 is that the immune evasion by SARS-CoV-2 prevents an adequate early adaptive immune response, allowing uncontrolled viral replication.…”
Section: Systemic Immune Responsesmentioning
confidence: 99%